(6x - 3) + (5x² - 4)
(-6x - 3) (5x² + 4)
(6x + 3) + (-5x² - 4)
-(6x - 3) - (5x² - 4)
-(6x + 3) + (5x² - 4)
-
=
=
=
=
6x ... 3 ... 5x² ...4
... 6x ... 3 ... 5x² ...4
... 6x ... 3 ... 5x² ...4
... 6x ... 3 ... 5x² ...4
6x ... 3 ... 5x²...4
... est ce que je peut avoir les réponses du 2 svp
![6x 3 5x 4 6x 3 5x 4 6x 3 5x 4 6x 3 5x 4 6x 3 5x 4 6x 3 5x 4 6x 3 5x 4 6x 3 5x 4 6x 3 5x 4 6x 3 5x4 Est Ce Que Je Peut Avoir Les Réponses Du 2 Svp class=](https://fr-static.z-dn.net/files/d89/8ef87bf8de0b89314067a210be3955b2.png)